Corporate Social Responsibility (CSR) and its Impact on Brand Loyalty in the Modern Business Landscape - Azeb Mesfin; Tirunesh Dibaba; Ewodros Adhanom Ghebreyesus (Universitas Kristen Indonesia Toraja, 2024)
Corporate Social Responsibility (CSR) has become an essential strategy for enhancing brand loyalty. This paper analyzes how CSR initiatives influence consumer trust and loyalty across various industries. Case studies from global brands provide practical insights into successful CSR implementation.